Fig. 3 in Distribution, prevalence and intensity of moose nose bot fly (Cephenemyia ulrichii) larvae in moose (Alces alces) from Norway ... - Rolandsen, Christer M.; Madslien, Knut; Ytrehus, Bjørnar; Hamnes, Inger Sofie; Solberg, Erling J.; Mysterud, Atle; Vikøren, Turid; Våge, Jørn; Hanssen, Oddvar; Miller, Andrea L. (Zenodo, 2021)
Fig. 3. The predicted parasite intensity of moose nose bot fly larvae for harvested calves (red), yearlings (blue) and adult (green) moose in central and southern Norway. Predictions from the highest ranked intensity model with study area and age group. (For interpretation of the references to colour in this figure legend, the reader is referred to the Web version of this article.) ... : Published as part of Rolandsen, Christer M., Madslien, Knut, Ytrehus, Bjørnar, Hamnes, Inger Sofie, Solberg, Erling J., Mysterud, Atle, Vikøren, Turid, Våge, Jørn, Hanssen, Oddvar & Miller, Andrea L., 2021, Distribution, prevalence and intensity of moose nose bot fly (Cephenemyia ulrichii) larvae in moose (Alces alces) from Norway, pp. 120-126 in International Journal for Parasitology: Parasites and Wildlife 15 on page 123, DOI: 10.1016/j.ijppaw.2021.04.012, http://zenodo.org/record/13267198 ...